Long-term antipsychotic and benzodiazepine use and brain volume changes in schizophrenia: The Northern Finland Birth Cohort 1966 study - Huhtaniska, Sanna; Jääskeläinen, Erika; Heikka, Tuomas; Moilanen, Jani; Lehtiniemi, Heli; Tohka, Jussi; Manjon, Jose; Coupé, Pierrick; Björnholm, Lassi; Koponen, Hannu; Veijola, Juha; Isohanni, Matti; et al. (Psychiatry Research: Neuroimaging, 2017)
International audience